Writing for science and engineering : papers, presentations, and reports - Silyn-Roberts, Heather (Butterworth-Heinemann, 2000)
Are you a post-graduate student in Engineering, Science or Technology who needs to know how to: Prepare abstracts, theses and journal papers Present your work orally Present a progress report to your funding body Would you like some guidance aimed specifically at your subject area? ... This is the book for you; a practical guide to all aspects of post-graduate documentation for Engineering, Science and Technology students, which will prove indispensable to readers. Writing for Science and Engineering will prove invaluable in all areas of research and writing due its clear, concise style. The practical advice contained within the pages alongside numerous examples to aid learning will make the preparation of documentation much easier for all students.
Keywords: Technical writing.; elektronické knihy; electronic books